Testosterone-Dependent Transgene Expression in the Liver of the CAG-lacZ Transgenic Rat - Sereemaspun, Amornpun (Gene Expr, 2018)
Many endogenous gene expressions in the liver are well known to be predominant in males, compared with those of females. In contrast, the fate of hepatic transgene expression between sexes is not fully understood. Here we studied whether sex hormones changed hepatic transgene expression in the ubiquitous CAG promoter-driven lacZ transgenic (Tg) rat. Both sexes of CAG-lacZ Tg rats received gonadectomy. Liver biopsy was taken weekly to determine the change of transgene expression. Histological result of adult males showed mosaic lacZ expression but it was negative in adult females, while livers in neonatal stage showed comparable expression of lacZ. Other organs exhibited equal expression in both sexes. At 2 weeks after castration, lacZ expression in male liver was significantly decreased and became negative after 4 weeks while no significant difference was observed in the lacZ expression pattern in other organs. After ovariectomy, lacZ expression in female liver remained undetectable. Moreover, testosterone treatment to gonadectomized rats of both sexes could enhance lacZ expression in the liver. In summary, we report that CAG-lacZ Tg rats demonstrate sexual dimorphism of transgene expression specifically only in the liver. Testosterone administration mediated upregulation of liver lacZ expression. Our findings suggested that androgen, especially testosterone, plays an important role in the hepatic transgene expression.